139k views
1 vote
If f(x) = 6x^2 - 2x - 5 and g(x) = -2x^2 + 3x - 1, find (f-g) (x)

User SARI
by
5.7k points

2 Answers

5 votes

Hey there! I'm happy to help!

To find (f-g)(x), we simply subtract the function g from the function f.

6x²-2x-5-(-2x²+3x-1)

We combine like terms.

6x²+2x²=8x²

-2x-3x=-5x

-5-(-1)=-5+1=-4

Therefore, (f-g)(x)=8x²-5x-4

Have a wonderful day! :D

User Yuki  Yoshida
by
6.5k points
6 votes

Answer: (f-g)(x)=8x²-5x-4

Explanation:

(f-g)(x) means to subtract f(x) and g(x). Since we are given f(x) and g(x), we can directly subtract them.

(f-g)(x)=6x²-2x-5-(-2x²+3x-1) [distribute -1]

(f-g)(x)=6x²-2x-5+2x²-3x+1 [combine like terms]

(f-g)(x)=8x²-5x-4

Now, (f-g)(x)=8x²-5x-4 is our answer.

User Donnalee
by
6.1k points